The 2019 General Election and The Politics of Inconclusive Election in Nigeria: A Review of The Affected States - Babayo Sule; Usman Sambo (Khazanah Sosial, 2020)
Elections are usually accompanied with controversies and irregularities in Nigeria emanating from several factors such as the procedures, regulations, nature of political culture and political gameplay in the country and elites’ attitudes towards power. The 2019 Gubernatorial election in Nigeria was enshrouded in controversies, malpractices and inconsistencies because of the Independent National Electoral Commission (INEC) guidelines for the conduct of election which provided for inconclusive elections in some circumstances. This study examined critically some states in Nigeria that are affected by the politics of inconclusive elections where the elections were extended for additional two weeks due to some issues that could not allow for the final declaration after the first date of the election. The inconclusive election heralded several problems and a setback to election in Nigeria because of recorded violence, malpractices, rigging and other related obstacles. The research employed a qualitative methodology of data collection and analysis. Both primary and secondary sources were used for data collection. The primary sources involved an in-depth interview, participant observation and reference to INEC’s documented data. The secondary data used were books, journals, newspapers, internet sources and reports. The data collected were discussed using content analysis for analytical interpretations. The study discovered that the guideline for the conduct of the 2019 General Election which stipulated for the provision of inconclusive election created several inconclusive elections in some states like Adamawa, Bauchi, Benue, Kano, Plateau and Sokoto which later was followed by irregularities and violence. The work recommends among others that such criteria should be abandoned and declare any contestant that fulfill the minimum criteria as returned elected.